If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -2 = 12y + -13 Reorder the terms: -2 + 2y = 12y + -13 Reorder the terms: -2 + 2y = -13 + 12y Solving -2 + 2y = -13 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. -2 + 2y + -12y = -13 + 12y + -12y Combine like terms: 2y + -12y = -10y -2 + -10y = -13 + 12y + -12y Combine like terms: 12y + -12y = 0 -2 + -10y = -13 + 0 -2 + -10y = -13 Add '2' to each side of the equation. -2 + 2 + -10y = -13 + 2 Combine like terms: -2 + 2 = 0 0 + -10y = -13 + 2 -10y = -13 + 2 Combine like terms: -13 + 2 = -11 -10y = -11 Divide each side by '-10'. y = 1.1 Simplifying y = 1.1
| -5-2y=6-6y | | 2x-7/3=11 | | 6x^4/3 | | 15w-60=-12w-35 | | -2/3x+3(5x+40)=-34 | | 2(3x-2)=84 | | 7x-3=-19+3x | | 110+7x= | | 2/(q-1)=3/(q-2) | | 9x+10y=3660 | | -9y-11=12 | | 0=-10-5X^2-27X | | 72+4x= | | 64x^2-2x+1= | | 10k^2=-12 | | 32=32c | | 19-50x= | | c=15385+85 | | p=-10x^2+750x+-9000 | | -4+20=36 | | 10=2x-20 | | 3x-6(-1/3+8)=-3 | | X(X-16)-63=0 | | 2x+6x-80=112 | | 92+78x= | | 0.5x+2.1=0.9x-0.3 | | B-7+2b=31 | | .50x+.25(60)=.25(82) | | 1/2=m-1/8 | | 49+3x= | | 2(5x+20)-4x= | | 3x^2y+6xy+9xy^2=0 |